MENINGKATKAN MOTIVASI DAN KARAKTER WASAKA MENGGUNAKAN MODEL PROJECT BASED LEARNING DAN TALKING STICK TERINTEGRASI STEM PADA MUATAN IPA KELAS VB SDN-SN SUNGAI MIAI 5 BANJARMASIN - Syafira Salsabila; Muhsinah Annisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem contained in this study is the low learning outcomes of science due to the lack of student learning motivation, the low religious character during prayer activities and the low character of hard work in learning activities. The solution to the problem in this study is to use the Project Based Learning and Talking Stick models integrated with STEM. The purpose of this study is to describe student motivation, hard work and religious characters in science content of Theme 8 Environment of Our Friends in class VB students of SDN-SN Sungai Miai 5. The research used is class action research, using two cycles, namely cycle I and cycle II involving 34 students of Class VB SDN-SN Sungai Miai 5. The results of this study prove that using the Project Based Learning and Talking Stick models integrated with STEM can increase student motivation to learn, character and understanding of science concepts. This can be seen from the results of motivation research in cycle I of 64.7% (22 students) and in cycle II increased to 94.1% (32 students). While the results of research on religious character and hard work in cycle I were 70.6% (24 students) and increased in cycle II which was 97.1% (33 students).